Ictericia neonatal, factores de riesgo y fototerapia en el Hospital General Julius Doepfner. - Hurtado Alverca, Juan Daniel (2018)
Neonatal icterus is one of the main causes of hospital admission with neonatal care, which occurs in 60 to 70% of newborns. This study determined the percentage of the diagnosis of neonatal icterus, the risk factors associated with the diagnosis, the levels of bilirubinemia in which the use of phototherapy was decided in relation to the age of the neonate, the type of phototherapy and time that was used to solve the icteric picture in relation to the diagnosis. This study was a descriptive type, where a sample of 73 patients with a diagnosis of neonatal icterus due to indirect hyperbilirubinemia was used. It was determined that neonatal icterus constituted the 57.9% in relation to the other causes of hospital discharge of neonatology. The most important risk factors associated with the diagnosis were: the masculine gender 54.79% (n = 40), the incompatibility of blood group ABO 31, 51% (n = 23) and insufficient exclusive breastfeeding 27.40% (n = 20). The most common age of neonatal icterus presentation was neonates with more than 72 hours of life, 53.46% (n = 39), with bilirubinemia values between 17.1 and 19.4 mg / dL. The predominant diagnosis was multifactorial neonatal icterus, 67.12% (n = 49), using simple phototherapy in 60.27% (n = 44), for the time of 1 to 2 days, 47.95% (n = 35). Key words: icterus, hyperbilirubinemia, bilirubinemia, phototherapy.